The Routledge handbook of religions and global development - Tomalin, Emma (Routledge international handbooks, 2015)
"This Handbook provides a cutting-edge survey of the current state of research on religions and development and interactions between religions and development. It uniquely looks at religions in context when thinking about their relationships to development. Different religious traditions are situated within actual locations and case studies thus allowing a better understanding of their relationships to development"--